Review of the African catfish genus Andersonia (Teleostei: Siluriformes) - Ferraris, Carl J.; Vari, Richard P. (Zootaxa, 2012)
Fishes of the catfish genus Andersonia (Amphiliidae, Doumeinae) are distributed widely across the northern sub-Saharanportion of Africa that is called the Nilo-Sudan Bioregion. Recent literature indicated that either one or two species of An-dersonia occur in the four drainage basins (upper Niger, upper Nile, Omo, and Lake Chad) in which the genus has beenfound. Our study failed to find any differences in the samples from those basins, as we therefore treat them as populationsof a single species, A. leptura, which is redescribed based on extensive series of specimens from across its range. The ge-nus Andersonia is retained as valid at this time, based on the lack of clear evidence of the phylogenetic position of A. lep-tura within the Doumeinae. However, a broader sampling of taxa, especially among species currently placed in the genus Phractura, may require a change to that assignment.